2015
DOI: 10.1111/nep.12383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrarenal renin‐angiotensin system activity in diabetic versus non‐diabetic patients with overt proteinuria

Abstract: Consistently elevated uRenin in DN, regardless of the amount of proteinuria, indicates that intrarenal RAS activity may be higher in DN compared to NDN in patients with overt proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…-Lower eGFR is associated with higher UAGT (Terami et al, 2013;Satirapoj et al, 2014;Zhuang et al, 2015). -Lower eGFR is not associated with higher UAGT (Park et al, 2015b).…”
Section: Diabetic Kidney Diseasementioning
confidence: 89%
“…-Lower eGFR is associated with higher UAGT (Terami et al, 2013;Satirapoj et al, 2014;Zhuang et al, 2015). -Lower eGFR is not associated with higher UAGT (Park et al, 2015b).…”
Section: Diabetic Kidney Diseasementioning
confidence: 89%
“…Therefore, the intracellular degradation system may be important in maintaining podocyte homeostasis and integrity. At the same time, the proximal convolute tubular cells (PCT) [7][8][9] are also vulnerable to high glucose with increased production of reactive oxygen species (ROS) via increased deposition of iron in lysosomes (Proximal Tubular Theory). Podocytes and PCT cells have evolved several mechanisms to face stress and to maintain cellular homeostasis, such as the anti-oxidative stress response and the endoplasmic reticulum (ER) stress response.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several previous studies have shown the presence of RAS components in the kidney and demonstrated that uAGT and urinary rennin can directly reflect the activity of intrarenal RAS. [7][8][9][10] The role of intrarenal RAS in AKI remains unclear, thus, the aim of this work was to determine the effect of intrarenal RAS on the occurrence of AKI in patients undergoing cardiac surgery with cardiopulmonary bypass.…”
Section: Observational Studymentioning
confidence: 99%